2021
DOI: 10.1002/btm2.10243
|View full text |Cite
|
Sign up to set email alerts
|

Oral drug delivery for immunoengineering

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 136 publications
(258 reference statements)
0
3
0
Order By: Relevance
“…The immune responses are mainly initiated in the intestine, where the majority of vaccine uptake and drug absorption occur [ 167 , 168 ]. The intestine consists of several layers, including the mucus layer, water layer, epithelial layer, basement membrane/Peyer’s patches, and lymph nodes [ 169 ]. The epithelial layer is composed of enterocytes, goblet cells, and microfold cells (M cells), which are joined together by tight junctions that prevent the movement of molecules through paracellular and transcellular routes [ 169 , 170 , 171 ].…”
Section: Administration Of Non-invasive Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…The immune responses are mainly initiated in the intestine, where the majority of vaccine uptake and drug absorption occur [ 167 , 168 ]. The intestine consists of several layers, including the mucus layer, water layer, epithelial layer, basement membrane/Peyer’s patches, and lymph nodes [ 169 ]. The epithelial layer is composed of enterocytes, goblet cells, and microfold cells (M cells), which are joined together by tight junctions that prevent the movement of molecules through paracellular and transcellular routes [ 169 , 170 , 171 ].…”
Section: Administration Of Non-invasive Vaccinesmentioning
confidence: 99%
“…The intestine consists of several layers, including the mucus layer, water layer, epithelial layer, basement membrane/Peyer’s patches, and lymph nodes [ 169 ]. The epithelial layer is composed of enterocytes, goblet cells, and microfold cells (M cells), which are joined together by tight junctions that prevent the movement of molecules through paracellular and transcellular routes [ 169 , 170 , 171 ]. Enterocytes, the most abundant cells in the intestinal epithelium (constituting up to 80% of the local cell population), transport antibodies through transcytosis using the neonatal Fc receptor (FcRn) and form antibody–antigen complexes [ 172 , 173 ].…”
Section: Administration Of Non-invasive Vaccinesmentioning
confidence: 99%
“…Immunoengineering approaches have made a great impact on generating techniques for anti-inflammatory applications. [1][2][3][4][5][6][7] Immunoengineering via delivery of metabolites is an emerging area of research, which can have great implications in treatment of various autoimmune diseases and disorders associ-ated with inflammation. [8][9][10] We previously demonstrated that glycolytic inhibition of innate immune cells, such as dendritic cells (DCs), along with the delivery of a self-antigen, via antiinflammatory alphaketo-glutarate (aKG) based microparticles, can lead to antigen-specific immune suppression in collageninduced arthritis (CIA) mice.…”
Section: Introductionmentioning
confidence: 99%